Prevent Domestic Violence: Reconstruction Wife Right to Freedom of Opinion and Expressions - Jenny Rahayu Afsebel Situmorang; Susanti, Vinita (Communicare : Journal of Communication Studies, 2022)
The wife is one of the potential victims of domestic violence. In patriarchal culture and social construction norms, the wife must obey all of their husband’s requests. Hence, they became vulnerable and got physical, sexual, economic, and many forms of domestic violence. Based on radical feminist theory, human rights concepts, and interpersonal communication theory, this article builds the idea to prevent domestic violence for wives by reconstructing their rights to freedom of opinion and expression. This research-based is on a literature review from scientific articles, books, and reports. After it, analyze with standpoint feminism. The result is that two points. First, in cultural and logical patriarchal, wives need interpersonal communication training to get equality when talking with their husbands. Second, reconstruction about wives’ awareness about freedom to opinion and expressions is necessary, so they do not fear to say no to their husbands and love themselves first. Finally, to prevent domestic violence against wives needs implementation of freedom to opinion and expressions in everyday life. Keywords: domestic violence; freedom to opinion and expressions; radical feminist theory, interpersonal communication theory; standpoint feminism